Operational expert system applications in Canada - Suen, Ching Y.; Shinghal, Rajjan, 1945- (Pergamon Press, 1991)
This book is part of a new series on operational expert systems worldwide. Expert systems are now widely used in different parts of the world for various applications. The past four years have witnessed a steady growth in the development and deployment of expert systems in Canada. Research in this field has also gained considerable momentum during the past few years. However, the field of expert systems is still young in Canada. This book contains 13 chapters contributed by 31 experts from both universities and industries across Canada covering a wide range of applications related to electric power and circuit boards, health and medicine, the legal field, transportation and decision making.